2022
DOI: 10.1111/vde.13131
|View full text |Cite
|
Sign up to set email alerts
|

The stability and in vitro antibacterial efficacy of enrofloxacin and gentamicin solutions against Staphylococcus pseudintermedius over 28 days

Abstract: Background Many clinicians prepare compounded otic solutions to treat otitis externa (OE). Research evaluating the stability and antimicrobial efficacy of these solutions is limited. Hypothesis/Objectives This study determined the chemical stability and in vitro bactericidal efficacy of compounded solutions of enrofloxacin and gentamicin during storage for 28 days. Materials and methods Solutions of enrofloxacin (10 mg/mL, 1%) and gentamicin (3 mg/mL, 0.3%) were prepared with normal saline and 1 mg/mL dexameth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Metry et al confirmed enrofloxacin’s stability, with no significant changes over 28 days at room temperature [ 48 ]. Marx et al, Park et al, and Petritz et al conducted additional tests at room temperature, finding enrofloxacin stable over 7 days [ 32 ], 28 days [ 34 ], and 56 days [ 33 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metry et al confirmed enrofloxacin’s stability, with no significant changes over 28 days at room temperature [ 48 ]. Marx et al, Park et al, and Petritz et al conducted additional tests at room temperature, finding enrofloxacin stable over 7 days [ 32 ], 28 days [ 34 ], and 56 days [ 33 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Like florfenicol, enrofloxacin showed considerable stability, with 88.7% of the initial concentration detectable on average by day 12 in both UPW solution and concentrations diluted in TSB. Okerman et al found more than 90% of the initial concentration intact after six months at −20 [32], 28 days [34], and 56 days [33], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated in the results of our study, the S. aureus clinical isolate was resistant to the most frequently used or first-line antibiotic prescribed for otitis externa infection (gentamicin). Thus topical and oral antibiotics (gentamicin and enrofloxacin) are frequently used in canine bacterial ear infections, and resistance is a significant concern [72]. An increasing antimicrobial resistance in the Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 99%